Climate change and its impact on the Malaysian stock index / Tay Bee Hoong, Norhasniza Mohd Hasan Abdullah and Masitah Omar - Tay, Bee Hoong; Mohd Hasan Abdullah, Norhasniza; Omar, Masitah (Universiti Teknologi MARA, Kedah, 2025)
Climate change poses significant risks to the financial market. There are significant research concerns surrounding this matter. This paper aims to study the impact of climate change on the Malaysian stock index. Considering the time series data of 43 years (1980 to 2022), regression analysis is implemented to investigate the correlation of macroeconomic variables such as gross domestic product, inflation rate, interest rate, and climate change indicator with the Malaysia Stock Index, which is represented by the FTSE Bursa Malaysia KLCI Price Index. The findings revealed that both gross domestic product and climate change indicate positive and significant correlations with the Malaysian stock index. In contrast, the inflation and interest rates were negatively correlated with the stock index, suggesting that higher inflation and a higher interest rate may deteriorate stock performance. This study contributes to the existing literature by providing a better grasp to investors in making decisions for equity investment in emerging markets.